PERAN BUDAYA ORGANISASIONAL DALAM MEMEDIASI PENGARUH KOMPETENSI KOMUNIKASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN (Studi Pada Dinas Pariwisata DIY) - Merlyn Kurniawati (Universitas Nusa Cendana, 2016)
Technology and Science development and globalization have made changes and create a newparadigm in workplace. An organization was not only pursuing higher productivity, but also paidattention towards performance in its achievement process. Performance was a key factor ofindividual and organization in order to achieve productivity. This research attempt to examinesome factors that influence Employee’s Performance. Communication Competence which is onebasic function of management in organization was important part in order to supporting employee’swork activities in organization. Beside Communication Competence, other factor which able toproduce optimal performance was Emotional Intelligence. Emotional intelligence gives possibilityon better understanding of the others so it more likely will create harmonic relationship. Other thanboth factors above, Organizational Culture also was one factor that makes improvement ofemployee’s performance. This research was conducted in Yogyakarta entitled Role ofOrganizational Culture on Mediating Communication Competence and Emotional IntelligenceInfluence towards Employee’s Performance on Tourism Official of Yogyakarta Special Region. Thedata collection tool used in this research was questionnaire. While data analysis technique used wasPartial Least Squares (PLS). The result revealed that not all hypotheses in this research havesupport. Variables of Communication Competence, Emotional Intelligence and OrganizationalCulture have significantly influence towards Employee’s Performance. While Organization Culturewas not mediating Communication Competence influence towards Employee’s Performance,conversely, it has been mediating Emotional Intelligence towards Employee’s Performance.Keywords: Communication Competence, Emotional Intelligence, Organizational Culture,Employee’s Performance.PENDAHULUANSektor pariwisata merupakan salah satu sektor andalan pemerintah untukmenghasilkan devisa